Universal and culture-specific aspects of psychophysiological emotional-related responses to music : a cross-cultural study - Mavrolampados, Anastasios (2019)
Previous cross-cultural studies in music and emotion have mostly focused on emotion recognition. As a result, the impact of enculturation on music-induced emotions remains largely unexplored. In the general literature beyond music, cross-cultural studies have suggested that cultural learning is affecting differently certain components of emotion. Physiological responses show similar patterns of activity across cultures, whereas self-reports of experienced emotion have more variation. Collectivist cultures have been shown to report lower levels of experienced emotion compared to individualistic cultures, and this has often been investigated by comparing East Asian and Western groups. To test these findings in a music setting, a cross-cultural study was conducted using Finnish, Greek, and Chinese participants. Instrumental excerpts of Western, Greek, and Chinese music were selected from previous studies that rated them for the emotions they conveyed. Self-reports were used to collect ratings of valence, arousal, intensity, and familiarity, along with measures of physiological activity (heart rate, skin conductance, and respiratory rate). Results showed similar levels of familiarity with Western music across groups. Self-reports revealed substantial group differences for valence, arousal, and intensity, suggesting that subjective feeling is greatly influenced by familiarity and cultural factors. No significant differences in physiology were found, supporting the idea that autonomic nervous system responses to music are more universal. Excerpts conveying negative emotions showed more variation across groups and had lower overall consistency, indicating culture-specific associations with unpleasant emotions that not always transcend across cultures. Contrary to studies with other types of stimuli, collectivist cultures did not report lower levels of experienced emotion, suggesting that individualism-collectivism might not be as relevant in a music listening setting.